Revisiting Third Party Funds and Non-Performing Loans on Profitability Before, During, and After COVID - Revfitra Mutahar Paradigma; Eduardus Suharto (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study was conducted to analyze the effect of third party funds and non performing loans on profitability. The study was conducted using annual reports that had been made by state-owned banks for the period 2019-2024. This research is tested using data panel with help from Eviews13 program. Results of this research shows that TPF have a moderate effects on ROA and NPL have a small negative effects on ROA.